Response of Cucumis sativus L.’s Growth and Harvest to Variations in Soaking Time and Plant Growth Promoting Rhizobacteria Concentration - Erviyana Windiastuti; Muhammad Hajji Ramadhan; Visi Tinta Manik; Fitri Kurniati; Yaya Sunarya (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Cucumber (Cucumis sativus L.) has numerous properties, making it a potential dietary, medicinal, and cosmetic element. As accordingly, organic methods must be implemented to enhance cucumber productivity. Plant Growth Promoting Rhizobacteria (PGPR) is used as biologic fertilizer and biological control agent. Seed priming with PGPR was the strategy utilized in this experiment. To optimize this strategy, this study must be undertaken to identify the reaction of seed priming PGPR Bacillus subtilis and Pseudomonas fluorescens to Cucumis sativus L. growth and yield. The study design employs a split-plot design with two components, two variations of soaking time duration and four variations of concentration of PGPR. The plant’s height, the amount of leaves, and dry weight of the root were all noted as the plant growth parameters observed. The harvest criteria observed included the quantity and weight of fruits per plant. The variance approach (F test) was used to assess the observations. The Least Significant Difference (LSD) test is subsequently applied to evaluate the differences throughout treatments at a significant threshold of 5%.. Growth and yield parameters responded differently in each treatment. However, all of the results obtained following statistical testing revealed that the reaction was not significantly different. This study gives vital information for farmers in optimizing cucumber production and implementing organic farming practices by employing PGPR as a biological fertilizer, indicating that further land selection is required.